PENDEKATAN INOVATIF UNTUK PEMBELAJARAN VISUAL: MENERAPKAN CAPCUT DAN CANVA UNTUK SISWA KANISIUS - Maria Atik Sunarti Ekowati; Kristyana Dananti (LPPM Universitas Nusa Mandiri, 2026)
Along with the development of digital technology, visual learning media has become an effective method for increasing students' understanding and involvement in the learning process. This community service aims to introduce and implement two graphic design applications, namely Capcut and Canva, as tools to increase the effectiveness of visual learning among students at Kanisius School. This activity involves training teachers and students to utilize these two applications in creating visual-based learning materials, such as educational videos, infographics and creative presentations. The expected result of this service is to increase students' skills in presenting learning material in an interesting and easy to understand manner, as well as increasing student motivation and interaction in the learning process. Apart from that, it is hoped that the use of Capcut and Canva can provide a more interactive and creative learning experience for students, as well as enrich existing teaching methods in schools. Evaluation was carried out through observation and feedback from participants to assess the extent to which the use of this tool was able to improve the quality of visual learning at Kanisius. The results of this service show an increase in students' understanding of the subject matter as well as an increase in students' digital skills that can be applied in a wider educational context.